Estuary–ocean connectivity: fast physics, slow biology. (29th November 2016) - Raimonet, Mélanie; Cloern, James E.
Abstract: Estuaries are connected to both land and ocean so their physical, chemical, and biological dynamics are influenced by climate patterns over watersheds and ocean basins. We explored climate‐driven oceanic variability as a source of estuarine variability by comparing monthly time series of temperature and chlorophyll‐ a inside San Francisco Bay with those in adjacent shelf waters of the California Current System (CCS) that are strongly responsive to wind‐driven upwelling. Monthly temperature fluctuations inside and outside the Bay were synchronous, but their correlations weakened with distance from the ocean. These results illustrate how variability of coastal water temperature (and associated properties such as nitrate and oxygen) propagates into estuaries through fast water exchanges that dissipate along the estuary. Unexpectedly, there was no correlation between monthly chlorophyll‐ a variability inside and outside the Bay. However, at the annual scale Bay chlorophyll‐ a was significantly correlated with the Spring Transition Index (STI) that sets biological production supporting fish recruitment in the CCS. Wind forcing of the CCS shifted in the late 1990s when the STI advanced 40 days. This shift was followed, with lags of 1–3 years, by 3‐ to 19‐fold increased abundances of five ocean‐produced demersal fish and crustaceans and 2.5‐fold increase of summer chlorophyll‐ a in the Bay. These changes reflect a slow biological process of estuary–ocean connectivity operating through the immigration of fish and crustaceans that prey on bivalves, reduce their grazing pressure, and allow phytoplankton biomass to build. We identified clear signals of climate‐mediated oceanic variability in this estuary and discovered that the response patterns vary with the process of connectivity and the timescale of ocean variability. This result has important implications for managing nutrient inputs to estuaries connected to upwelling systems, and for assessing their responses to changing patterns of upwelling timing and intensity as the planet continues to warm. Abstract : We explored climate‐driven oceanic variability as a source of estuarine variability by comparing monthly temperature and chlorophyll‐a inside San Francisco Bay with those in adjacent shelf waters. We identified clear signals of climate‐mediated oceanic variability in this estuary that depended on the process of connectivity and the time scale of ocean variability. This result has important implications for managing nutrient inputs to estuaries and for assessing their responses to climate change.